2021
DOI: 10.3389/fcimb.2021.639144
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophil Extracellular Traps in Periodontitis

Abstract: Periodontitis is a chronic, destructive disease of periodontal tissues caused by multifaceted, dynamic interactions. Periodontal bacteria and host immunity jointly contribute to the pathological processes of the disease. The dysbiotic microbial communities elicit an excessive immune response, mainly by polymorphonuclear neutrophils (PMNs). As one of the main mechanisms of PMN immune response in the oral cavity, neutrophil extracellular traps (NETs) play a crucial role in the initiation and progression of late-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 124 publications
0
23
0
Order By: Relevance
“…The production of NETs contributes to the clearance of pathogens. Excessive NETs production may cause autogenic immune diseases such as systemic lupus erythematosus [ 18 , 19 ]. Previous studies have found neutrophil enrichment in human subjects with early AMD and a model of AMD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production of NETs contributes to the clearance of pathogens. Excessive NETs production may cause autogenic immune diseases such as systemic lupus erythematosus [ 18 , 19 ]. Previous studies have found neutrophil enrichment in human subjects with early AMD and a model of AMD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophils from people with DM overexpress a key enzyme in the formation of neutrophil extracellular traps (NETs) [ 183 ]. NETosis has been involved in the pathogenesis of periodontitis [ 184 ] and DM-induced enhanced NETosis may promote inflammation and negatively affect the immune defense in the periodontal space.…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%
“…Lack of PR3 and deficient processing of hCAP-18 in neutrophils may play a role in the propensity of patients with PLS to develop periodontal disease [ 45 ]. It is known that neutrophils and NETs play a crucial role in preventing periodontitis [ 46 ]. Analyzing in depth the role of LL-37 in this context could generate important information that may help develop new effective treatments for this and other infectious diseases.…”
Section: Ll-37 In Other Autoimmune and Inflammatory Settingsmentioning
confidence: 99%